Die koinoniale konstruksie van 'n toerustingsprogram vir narratiewe pastorale sorg - JP Roux; DJ Kotzé (Acta Theologica)
A great variety of training programs are available for pastoral counsellor training from a modernis stance. This article contributes to this discourse by reflecting on the topic from a postmodern narrative discourse. The training narrative includes examples of training by means of multiple reflexive conversations concerning supervision and evaluation are also reflected upon. Being developed from this position the "program" is continuously under construction and should be viewed as a program constructed in time and context.